Body Mass Index, Glucose, and Triglycerides as Predictors of HbA1c Control in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Anwari, Farida; Octifani, Amellya (Chakra Brahmanda Lentera Institute, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease with rising global and national prevalence. Glycemic control, measured by glycated hemoglobin (HbA1c), is essential to prevent complications. Previous studies showed inconsistent findings on the effects of age, gender, body mass index (BMI), and triglycerides on HbA1c levels, with limited use of logistic regression. This study examined the influence of age, gender, BMI, glucose, and triglyceride levels on HbA1c control in Indonesian patients with T2DM. Methods: A cross-sectional study was conducted using secondary medical records of 55 T2DM patients treated at RA Basoeni Clinic, Mojokerto, Indonesia, in 2024. Inclusion criteria included patients aged ≥18 without anemia or hemoglobinopathy; patients with incomplete data were excluded. HbA1c values were estimated from average fasting and postprandial glucose over the past three months using the American Diabetes Association (ADA) 2019 conversion table. HbA1c status was categorized as controlled (≤6.5%) and uncontrolled (>6.5%). Logistic regression analysis was performed using SPSS version 25.0. The study adhered to STROBE reporting guidelines. Results: Of the 55 patients, 24 (43.6%) had controlled HbA1c and 31 (56.4%) had uncontrolled HbA1c. Logistic regression showed that BMI (OR=1.192, p=0.047), glucose (OR=1.026, p=0.044), and triglycerides (OR=1.017, p=0.049) significantly predicted HbA1c status. Age (p=0.837) and gender (p=0.884) were not significant predictors. The model explained 68.9% of the variance (Nagelkerke R²=0.689) with an overall classification accuracy of 83.6%.. Conclusion: BMI, glucose, and triglycerides are significant predictors of HbA1c control in T2DM patients, while age and gender are not. To improve glycemic outcomes, clinical management should prioritize weight regulation, glucose monitoring, and triglyceride control.